Penerapan Metode Analytical Hierarchy Process Dalam Mengetahui Kriteria Minat Masyarakat Terhadap Penggunaan Automated People Mover System - Santoso, Sugeng; Astriandari, Juni; Maulana, Taufik; Ramadhan, Aditya; Sumantri, Dicky (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2022)
PT. Angkasa Pura II Soekarno Hatta Airport branch office provides facilities in the form of an Automated People Mover System (APMS) or Skytrain. The facility is an unmanned flyover that functions as a facility in moving between terminals at Soekarno Hatta Airport. The Automated People Mover System (APMS) facility is connected to the airport train through an integrated building, making it easier for passengers to go to or from the Soekarno Hatta airport terminal. The purpose of this study was to determine the criteria for public interest in the use of the Automated People Mover System (APMS) based on the criteria used by researchers. The criteria of the research are aspects of ease/accessibility, comfort, security and time efficiency. The study used a mixed method approach in the form of collecting data from filling out questionnaires and interviews with a number of sources, namely experts in charge of service and facility Automated People Mover System (APMS). The methodology in this study uses the Analytical Hierarchy Process analysis tool super decision software version 2.10.0. The results of the study indicate that the criteria for public interest in the use of the Automated People Mover System (APMS) is to prioritize the convenience criteria over other criteria. The weight or value of the criteria used is the highest criterion is the comfort aspect with a weight of 37%, then the security aspect 22%, then the ease/accessibility aspect 21% and the time efficiency aspect 19%.Keywords - APMS, Soekarno Hatta Airport, Facility, AHP, Super Decisio